Program Book for Winter/Spring 2018 - Youth Employment Services (YES) (2018)

Recommendations from the Youth Unemployment Forum Held on December 5, 2017 - Youth Employment Services (YES) (2018)
In Quebec and indeed across Canada we are confronting the many and varied challenges of a rapidly evolving labour market. New technologies are developing at a rate that is challenging our institutions; globalization is bringing increasing unpredictability to economic systems; traditional management models are being disrupted by the growing sharing and gig economies. Youth may have adapted quickly to high-tech society, however it would be disastrous to assume they will adjust as easily to the trials of the Fourth Industrial Revolution. Today’s youth need innovative supports to help them to survive in and capitalize on the complexities of the future economy. While Québec youth have never been more highly educated or bilingual, young job seekers andemployers alike are frustrated. Not enough has been done to curb the outmigration of educated youth nor to create an equitable environment for underrepresented populations. It hardly matters that jobs may be available, if youth are not here or not able to connect with them. This is why, with support from Canadian Heritage, on December 5th, 2017 YES convened a daylong forum bringing together multiple sectors from throughout the province of Quebec, to develop a deeper understanding of the unique employment barriers faced by Quebec’s Official Language Minority Community (OLMC) youth.
Keywords: Official Language Minority Community (OLMC)

Turn into YES 12 : A Benefit Event and Silent Auction : Sponsorship Opportunity - Youth Employment Services (YES) (2018)